PTU-036 Endoscopic sphincteroplasty in combination with sphincterotomy; is it worth it?. (22nd June 2015) - Manning, C; deSilva, A; Brett, B; Sheikh, K
Abstract : Introduction: Endoscopic balloon sphincteroplasty (EBS) is an adjunct and possible alternative to sphincterotomy to remove biliary stones. EBS alone can be associated with complications like pancreatitis but can be safe and effective when combined with sphincterotomy. Reduced pancreatitis rates with a combined technique may relate to the force of dilatation being directed away from the pancreatic orifice. NSAIDs reduce the risk of post-procedure pancreatitis but there is insufficient data on its use specifically with combined technique. Method: A retrospective review of patients undergoing EBS in addition to sphincterotomy for management of stones. Objectives were to assess CBD clearance and complication rates, and review the outcome of rectal NSAID use. We identified 93 eligible cases – 10 were excluded due to insufficient data. Results: 30 of 41 index cases had successful clearance with EBS. 8 failed cases underwent further ERCP, 5 had upstaged balloon sphincteroplasty with successful clearance. For 32 of 42 repeat cases, this was the first EBS procedure. 22 of these were successful. Reasons for failed clearance were mainly poor tolerance/prolonged procedure/duodenoscope malfunction. Of a total of 22 failed cases, only 4 were due to large stones/difficult anatomy. The addition of EBS achieved higher clearance rates for stones <2 cm at both index and repeat ERCP. Immediate complications increased with balloon size. Stones >2 cm led to more complications and reduced clearance rates. No complications were seen when 'interval' sphincteroplasty was performed with balloon >15 mm. 15 cases developed complications, 11 were minor bleeds resolved at ERCP. 1 elderly patient had a significant delayed bleed requiring endoscopic haemostasis but developed fatal re-bleeding triggered by anticoagulation. There were 3 cases of post-ERCP biliary sepsis. A total of 39 of 83 cases received rectal diclofenac based on perceived risk of post procedure pancreatitis and risk of NSAID use. No cases of post-ERCP pancreatitis were seen. Conclusion: EBS with sphincterotomy appears safe and potentially prevents additional procedures. Complication rates are greater with balloons >15 mm or stones >2 cm at index procedure and suggests alternative modalities should be considered in such cases. 'Interval' sphincteroplasty >15 mm appears safer than use at index. Immediate complications encountered were largely minor except 1 patient who required repeat endoscopic haemostasis but had fatal re-bleed due to anticoagulation. The use of adrenaline to control haemostasis and prevent delayed bleeding appears effective. No cases of pancreatitis were seen in our cohort; this may signify a benefit in using NSAIDs post-ERCP where suitable but requires analysis with a larger patient cohort. Disclosure of interest: None Declared.